EFFECT OF DIGITAL COMIC LEARNING MEDIA ON THE LEARNING OUTCOMES OF EIGHTH GRADE STUDENTS AT SMP MUHAMMADIYAH 1 METRO - Dwianugraha, Ahmad Nur'Afief Dwianugraha (Jurusan P. IPS, FKIP, Universitas Mataram, 2025)
This study aims to determine the effect of QR code-based digital comic learning media on the learningoutcomes of eighth-grade students. The method used is quasi-experimental. Data collection techniqueswere carried out through pre-tests and post-tests, supported by questionnaires and observations. Dataanalysis techniques included descriptive statistical analysis, prerequisite tests, hypothesis testing, andN-Gain Score testing. The results of the study showed a significant difference between the experimentalclass that used QR code-based digital comic media and the control class that used PowerPoint slides.The N-Gain score for cognitive learning outcomes in the experimental class reached 70.17% in the highcategory, while the control class only reached 45.17% in the moderate category. Affective learningoutcomes were indicated by a coefficient of determination of 55.7%. In the psychomotor domain,observation results showed a percentage of 89.69% in the very good category for the experimentalclass, compared to 79.2% in the good category for the control class. Based on the results of this study,it can be concluded that the use of digital comic-based QR-Code learning media has a significant effecton improving students' cognitive, affective, and psychomotor learning outcomes in Pancasila Educationcompared to conventional learning media. Kata Kunci: Komik Digital; QR-Code; Hasil Belajar; Media Pembelajaran; Pendidikan Pancasila.